EVALUASI SISTEM DRAINASE DI RUAS JALAN UNLAM I DAN III BANJARBARU - Sofia, Elma; Fitriyani, Julecha; Fitriati, Ulfa; Nashrullah, Eddy; Widiastuti, Endah (Universitas Lambung Mangkurat, 2024)
This research intends to determine whether the capacity of existing drainage channels is still sufficient or not. The method of analysis used involved collecting rainfall data over the past 14 years (2010-2023) from the Class I Banjarbaru Climatology Station and obtaining the dimensions of the drainage channels from direct field measurements. From the results of the study, it was found that some of the drainage was unable to withstand the discharge plan, so redesign and new drainage design were needed. The planned channel dimensions for the redesigned drainage have a channel depth of 1 m and a planned width of 0.9 m. The planned channel dimensions for the new drainage have a channel depth of 0.9 m and a planned width of 0.7 m.